A photothermal-triggered nitric oxide nanogenerator combined with siRNA for precise therapy of osteoarthritis by suppressing macrophage inflammation. Issue 14 (22nd March 2019) - Chen, Xu; Liu, Yanan; Wen, Yayu; Yu, Qianqian; Liu, Jiawei; Zhao, Yingyu; Liu, Jie; Ye, Gang
Abstract : Although nitric oxide (NO) can be used to treat osteoarthritis (OA) by inhibiting inflammation, a method for the accurately controlled release of NO in inflammatory cells is still elusive. Abstract : Although nitric oxide (NO) can be used to treat osteoarthritis (OA) by inhibiting inflammation, a method for the accurately controlled release of NO in inflammatory cells is still elusive. Herein, photothermal-triggered NO nanogenerators NO-Hb@siRNA@PLGA-PEG (NHsPP) were constructed by assembling photothermal-agents and NO molecules within nanoparticles. In the NHsPP nanoparticles the hemoglobin (Hb) nanoparticles can act as a NO carrier which can absorb near-infrared light at 650 nm (0.5 W cm −2 ) and convert it into heat to trigger the release of NO. Moreover, after loading Notch1-siRNA, precise treatment can be achieved. Furthermore, using the synergistic effect of photothermal therapy, the NHsPP nanoparticles achieved simultaneous treatment with NO, siRNA and PTT. Through this combination therapy, the therapeutic effect of the NHsPP nanoparticles was significantly enhanced compared to the treatment groups using only NO, siRNA or PTT. This combination therapy inhibits the inflammatory response effectively by reducing the level of pro-inflammatory cytokines and the macrophage response. Subsequently, guided by dual-modal imaging, the NHsPP nanoparticles can not only accumulate effectively in OA mice, but can also reduce the inflammatory response and efficiently prevent cartilage erosion, without causing toxic side effects in the major organs. Therefore, this novel photothermal nanoparticle-based NO-releasing system is expected to be a potential alternative for clinical inflammatory disease therapy and may provide image guidance when combined with other nanotherapy systems.